Cost-Effectiveness of Preemptive Switching to Efavirenz-Based Antiretroviral Therapy for Children With Human Immunodeficiency Virus. (11th June 2019) - Desmonde, Sophie; Frank, Simone C; Coovadia, Ashraf; Dahourou, Désiré L; Hou, Taige; Abrams, Elaine J; Amorissani-Folquet, Madeleine; Walensky, Rochelle P; Strehlau, Renate; Penazzato, Martina; Freedberg, Kenneth A; Kuhn, Louise; et al.
Abstract: Background: The NEVEREST-3 (South Africa) and MONOD-ANRS-12206 (Côte d'Ivoire, Burkina Faso) randomized trials found that switching to efavirenz (EFV) in human immunodeficiency virus–infected children >3 years old who were virologically suppressed by ritonavir-boosted lopinavir (LPV/r) was noninferior to continuing o LPV/r. We evaluated the cost-effectiveness of this strategy using the Cost-Effectiveness of Preventing AIDS Complications–Pediatric model. Methods: We examined 3 strategies in South African children aged ≥3 years who were virologically suppressed by LPV/r: (1) continued LPV/r, even in case of virologic failure, without second-line regimens; continued on LPV/r with second-line option after observed virologic failure; and preemptive switch to EFV-based antiretroviral therapy (ART), with return to LPV/r after observed virologic failure. We derived data on 24-week suppression (<1000 copies/mL) after a switch to EFV (98.4%) and the subsequent risk of virologic failure (LPV/r, 0.23%/mo; EFV, 0.15%/mo) from NEVEREST-3 data; we obtained ART costs (LPV/r, 6–20/mo; EFV, 3–6/mo) from published sources. We projected discounted life expectancy (LE) and lifetime costs per person. A secondary analysis used data from MONOD-ANRS-12206 in Côte d'Ivoire. Results: Continued LPV/r led to the shortest LE (18.2 years) and the highest per-person lifetime cost (19 470). LPV/r with second-line option increased LE (19.9 years) and decreased per-person lifetime costs(16 070). Switching led to the longest LE (20.4 years) and the lowest per-person lifetime cost (15 240); this strategy was cost saving under plausible variations in key parameters. Using MONOD-ANRS-12206 data in Côte d'Ivoire, the Switch strategy remained cost saving only compared with continued LPV/r, but the LPV/r with second-line option strategy was cost-effective compared with switching. Conclusion: For children ≥3 years old and virologically suppressed by LPV/r-based ART, preemptive switching to EFV can improve long-term clinical outcomes and be cost saving. Clinical Trials Registration: NCT01127204 Abstract : Using the Cost-Effectiveness of Preventing AIDS Complications–Pediatric model to project clinical outcomes, costs, and cost-effectiveness, we show that preemptively switching to efavirenz in virologically suppressed children >3 years old receiving ritonavir-boosted lopinavir (LPV/r) is cost saving compared with continued LPV/r.